Breast feeding determinants on the first year of life of children in a city of Midwestern Brazil - França, Giovanny Vinícius Araújo de; Brunken, Gisela Soares; Silva, Solanyara Maria da; Escuder, Maria Mercedes; Venancio, Sonia Isoyama (Revista de Saúde Pública, 2007)
OBJECTIVE: To assess risk factors for breastfeeding discontinuation and weaning among children less than one year old. METHODS: A cross-sectional study was carried out in children under one year of age brought by their caregivers to immunization units in the city of Cuiabá, Midwestern Brazil, in 2004. Sampling first comprised drawing immunization units and then children in each unit were systematically drawn. Data was collected through semi-structured questionnaires applied to children's caregivers investigating social and demographic variables, as well as variables related to birth and maternal characteristics, pacifier use and feeding on the first day at home. Descriptive statistical and logistic regression analyses of risk factors by age group were conducted and odds ratios and 95% confidence intervals were estimated. RESULTS: A total of 920 children under one year of age were studied, of which 205 were less than 120 days old and 275 were less than 180 days old. Pacifier use, offering tea to children on their first day at home, and being a child of a mother with first or second grade schooling or primapara posed an increased risk for not being on exclusive breastfeeding at the age of 120 days. All these factors were also significantly associated in those under 180 days old, except tea offering, which was not investigated for this age group. Among children less than one year old, pacifier use was the only variable that remained significant. CONCLUSIONS: Social and cultural factors were determinants of breastfeeding status. Maternal education and awareness are crucial to prevent practices that can negatively affect breastfeeding.